Electrode surface modification using metallophthalocyanines and metal nanoparticles : electrocatalytic activity - Maringa, Audacity (Rhodes University, Faculty of Science, Department of Chemistry, 2015)
Metallophthalocyanines and metal nanoparticles were successfully synthesized and applied for the electrooxidation of amitrole, nitrite and hydrazine individually or when employed together. The synthesized materials were characterized using the following techniques: predominantly scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), electrochemistry and scanning electrochemical microscopy (SECM). Different electrode modification methods were used to modify the glassy carbon substrates. The methods include adsorption, electrodeposition, electropolymerization and click chemistry. Modifying the glassy carbon substrate with MPc (electropolymerization) followed by metal nanoparticles (electrodeposition) or vice versa, made a hybrid modified surface that had efficient electron transfer. This was confirmed by electrochemical impedance studies with voltammetry measurements having lower detection potentials for the analytes. This work also describes for the first time the micropatterning of the glassy carbon substrate using the SECM tip. The substrate was electrografted with 4-azidobenzenediazonium salt and then the click reaction was performed using ethynylferrocene facilitated by Cuâ º produced at the SECM tip. The SECM imaging was then used to show the clicked spot.
Keywords: Phthalocyanines; Nanoparticles; Electrocatalysis; Scanning electron microscopy; X-ray photoelectron spectroscopy; Electrochemistry; Scanning electrochemical microscopy